CONVERSATION ANALYSIS IN MADAGASCAR MOVIE - Qonaah Nuryan Arif; Esti Raihana (Sean Institute, 2023)
Conversation is the work of people to interact each other using language. Allthough all people do a conversation everyday, but in fact not all people know what aspects that exist when they are doing the conversation. If people really understand those aspects it will make the conversation become meaningfull and effetive. The research focuses on 3 aspects of conversation, those are turn-taking, adjency pairs and sequence. The main data of the research is a script of Madagascar 3:Europes’ most wanted. This movie was choosen because the language used in this movie represent the way people do conversation in daily life and has theme about friendship for help each other to reach a goal. This research used descriptive qualitative method to analyzed the data based on theory by Jhoan Cutting about Conversation Analysis. The data were video and script. Duration of this movie was 01..33.25 hour. The researcher analyzed all utterances from all dialogues used by all characters in the movie. The result of this reseacrh showed that there were 92 data of pattern of Conversation Analysis; 4 turn taking, 9 interruption, 17 overlap, 4 attributable silent, 34 preferred response, 19 disreferred response. Most dominant data is preferred response form aspect adjency pairs. A lot of response given by the hearer agreeable with what is desired by the speaker.